Evaluation of HIV viral load turnaround time in Moshi, Tanzania - Moirana, Elizabeth L; Muro, Eva Prosper; Kiwelu, Ireen Eliah; Kimaro, James; Manongi, Rachel; Theilgaard, Zahra; Katzenstein, Terese L (The Journal of Infection in Developing Countries, 2022)
Introduction: Viral load measurement is an important gold standard for monitoring anti-retroviral treatment among people living with human immunodeficiency virus. The optimal use of the viral load results for guiding antiretroviral therapy depends on timely availability of the results at the clinic. The objective of the current study was to evaluate the turnaround time and utilization of viral load results in the clinical decision process. Methodology: This was a retrospective cohort study which involved patients receiving cART from 1 August 2018 to 31 January 2017 at three clinics in Tanzania. Data was extracted from patient files at the clinics and relevant records were kept at the viral load determining laboratory. The data were analysed with the Statistical Package for Social Sciences version 20. Results: 445 subjects had a viral load in test results and 88% had a viral load of > 1,000 copies/mL. The median duration on the current regimen was five years. Median time between the clinics receiving the results and communicating them to the patients was 40 days. Shorter turnaround time was observed for patients with virological failure (p = 0.003). A higher prevalence of virological failure was found in patients monitored at the Kilimanjaro Christian Medical Centre (KCMC) compared to the two primary health clinics (p = 0.04). Conclusions: The median viral load turnaround time was longer than stipulated by the national Tanzanian guidelines. Interventions that may reduce viral load turn-around-time, including point of care viral load testing, are needed to optimise monitoring of anti-retroviral therapy.